First we need to convert the given equation to standard form, only then we can find the center and radius of the circle.
![x^{2} + y^{2} +18x+14y+105=0 \\ \\ x^{2} +18x+ y^{2}+14y=-105 \\ \\ x^{2} +2(x)(9)+ y^{2}+2(y)(7)=-105 \\ \\ x^{2} +2(x)(9)+ 9^{2} + [y^{2}+2(y)(7)+7^{2}] =-105+9^{2}+7^{2} \\ \\ (x+9)^{2}+ (y+7)^{2}=25 ](https://tex.z-dn.net/?f=%20x%5E%7B2%7D%20%2B%20y%5E%7B2%7D%20%2B18x%2B14y%2B105%3D0%20%5C%5C%20%20%5C%5C%20%0A%20x%5E%7B2%7D%20%2B18x%2B%20y%5E%7B2%7D%2B14y%3D-105%20%5C%5C%20%20%5C%5C%20%0A%20x%5E%7B2%7D%20%2B2%28x%29%289%29%2B%20y%5E%7B2%7D%2B2%28y%29%287%29%3D-105%20%5C%5C%20%20%5C%5C%20%0Ax%5E%7B2%7D%20%2B2%28x%29%289%29%2B%209%5E%7B2%7D%20%2B%20%5By%5E%7B2%7D%2B2%28y%29%287%29%2B7%5E%7B2%7D%5D%20%20%3D-105%2B9%5E%7B2%7D%2B7%5E%7B2%7D%20%20%5C%5C%20%20%5C%5C%20%0A%20%28x%2B9%29%5E%7B2%7D%2B%20%28y%2B7%29%5E%7B2%7D%3D25%20%20%0A%20%20)
The standard equation of circle is:
![(x-a)^{2} + (y-b)^{2}= r^{2}](https://tex.z-dn.net/?f=%28x-a%29%5E%7B2%7D%20%2B%20%28y-b%29%5E%7B2%7D%3D%20r%5E%7B2%7D%20%20)
with center (a,b) and radius = r
Comparing our equation to above equation, we can write
Center of circle is (-9, -7) and radius of the given circle is 5
Answer:
x = -7
Step-by-step explanation:
3x + 13 = -2x - 22
subtract 13 from both sides
3x = -2x - 35
Add 2x to both sides
5x = -35
Divide each side by 5
x = -7
The base of 6 is the same, so add 1/2+1/2 =1
6^1 = 6
When the bases are diffenrent and the exponents of a and b are the same, we can multiply a and b first:
a n ⋅ b n = (a ⋅ b) n
Example:
32 ⋅ 42 = (3⋅4)2 = 122 = 12⋅12 = 144
When the bases and the exponents are different we have to calculate each exponent and then multiply:
a n ⋅ b m
Example:
32 ⋅ 43 = 9 ⋅ 64 = 576
If the relationship between two quantities is a proportional relationship, this relationship can be represented by the graph of a straight line through the origin with a slope equal to the unit rate.